Wage determination, Global Value Chains and role played by wage bargaining schemes: The case of Poland - Nikulin, Dagmara; Wolszczak-Derlacz, Joanna (Economics and Business Review, 2022)
This study examines the linkages between GVC involvement and wages in Poland given different wage bargaining schemes. The analysis is based on microdata from the European Structure of Earnings Survey for Poland combined with sectoral data from the World Input-Output Database. In particular, two measures of GVC involvement were used: the share of foreign value added (FVA) to export and the measure of traditional offshoring. The institutional settings are represented by the wage bargaining scheme which reflects the level at which the collective pay is agreed. The results show that despite the lack of a significant relationship between the sectoral involvement in GVC and the level of wages in Poland, on average workers covered by the collective pay agreement receive higher wages. Moreover, the wage-GVC nexus is conditioned on the type of pay agreements: the positive wage effect from national agreements is eliminated for a certain range of GVC intensity.